Through bleaching and tsunami: Coral reef recovery in the Maldives. Issue 1 (15th September 2015) - Morri, Carla; Montefalcone, Monica; Lasagna, Roberta; Gatti, Giulia; Rovere, Alessio; Parravicini, Valeriano; Baldelli, Giuseppe; Colantoni, Paolo; Bianchi, Carlo Nike
Abstract : Graphical abstract: Highlights: Historical data are necessary to assess the effects of climate change on coral reefs. Data on the state of coral reefs were collected from 1997 to 2014 in the Maldives. Several descriptors and metrics allowed coral reef recovery complexity to be illustrated. According to the descriptor, recovery took 6–15 years or may even be considered unachieved. Abstract: Coral reefs are degrading worldwide, but little information exists on their previous conditions for most regions of the world. Since 1989, we have been studying the Maldives, collecting data before, during and after the bleaching and mass mortality event of 1998. As early as 1999, many newly settled colonies were recorded. Recruits shifted from a dominance of massive and encrusting corals in the early stages of recolonisation towards a dominance of Acropora and Pocillopora by 2009. Coral cover, which dropped to less than 10% after the bleaching, returned to pre-bleaching values of around 50% by 2013. The 2004 tsunami had comparatively little effect. In 2014, the coral community was similar to that existing before the bleaching. According to descriptors and metrics adopted, recovery of Maldivian coral reefs took between 6 and 15 years, or may even be considered unachieved, as there are species that had not come back yet.